2014
DOI: 10.3746/jkfn.2014.43.12.1801
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and DNA Damage Protective Activities of Freeze-Dried Blue Mussel (Mytilus edulis)

Abstract: Blue mussels (Mytilus edulis) are widely distributed among the world's oceans in various habitats. The purpose of this study was to investigate the effects of freeze-drying on the antioxidant and antigenotoxic activities of blue mussels collected in the Gyeongnam coast area of Korea. Raw (RM) and freeze-dried blue mussel flesh (FRM) were extracted with ethanol, methanol, and water. Antioxidant activities were evaluated on the basis of DPPH radical scavenging activity, oxygen radical absorbance capacity (ORAC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Kim et al [8] found that a hot water extract of blue mussel flesh showed 36.81% DPPH RSA at a concentration of 10 mg/mL. Lee et al [10] also reported that ethanol and methanol extract from raw or freeze-dried blue mussel powder showed significant DPPH RSA; however, the water extract at 25°C for 12 h did not show detectable DPPH RSA. These reports suggest that antioxidant materials in blue mussels are difficult to dissolve in cold water and relatively easy to dissolve in organic solvents and hot water.…”
Section: Concentration Of Blue Mussel Scw Extractmentioning
confidence: 99%
“…Kim et al [8] found that a hot water extract of blue mussel flesh showed 36.81% DPPH RSA at a concentration of 10 mg/mL. Lee et al [10] also reported that ethanol and methanol extract from raw or freeze-dried blue mussel powder showed significant DPPH RSA; however, the water extract at 25°C for 12 h did not show detectable DPPH RSA. These reports suggest that antioxidant materials in blue mussels are difficult to dissolve in cold water and relatively easy to dissolve in organic solvents and hot water.…”
Section: Concentration Of Blue Mussel Scw Extractmentioning
confidence: 99%